Inhibitor of cyclin-dependent kinase (CDK) interacting with cyclin A1 (INCA1) regulates proliferation and is repressed by oncogenic signaling - Bäumer, Nicole; Tickenbrock, Lara; Tschanter, Petra; Lohmeyer, Lisa; Diederichs, Sven; Bäumer, Sebastian; Skryabin, Boris V.; Zhang, Feng; Agrawal-Singh, Shuchi; Köhler, Gabriele; Berdel, Wolfgang E.; Serve, Hubert; et al. (The journal of biological chemistry, 2011)
The cell cycle is driven by the kinase activity of cyclin·cyclin-dependent kinase (CDK) complexes, which is negatively regulated by CDK inhibitor proteins. Recently, we identified INCA1 as an interaction partner and a substrate of cyclin A1 in complex with CDK2. On a functional level, we identified a novel cyclin-binding site in the INCA1 protein. INCA1 inhibited CDK2 activity and cell proliferation. The inhibitory effects depended on the cyclin-interacting domain. Mitogenic and oncogenic signals suppressed INCA1 expression, whereas it was induced by cell cycle arrest. We established a deletional mouse model that showed increased CDK2 activity in spleen with altered spleen architecture in Inca1−/− mice. Inca1−/− embryonic fibroblasts showed an increase in the fraction of S-phase cells. Furthermore, blasts from acute lymphoid leukemia and acute myeloid leukemia patients expressed significantly reduced INCA1 levels highlighting its relevance for growth control in vivo. Taken together, this study identifies a novel CDK inhibitor with reduced expression in acute myeloid and lymphoid leukemia. The molecular events that control the cell cycle occur in a sequential process to ensure a tight regulation, which is important for the survival of a cell and includes the detection and repair of genetic damage and the prevention of uncontrolled cell division.